2020
DOI: 10.3390/biom10101367
|View full text |Cite|
|
Sign up to set email alerts
|

Stress Granule Assembly Can Facilitate but Is Not Required for TDP-43 Cytoplasmic Aggregation

Abstract: Stress granules (SGs) are hypothesized to facilitate TAR DNA-binding protein 43 (TDP-43) cytoplasmic mislocalization and aggregation, which may underly amyotrophic lateral sclerosis pathology. However, much data for this hypothesis is indirect. Additionally, whether P-bodies (PBs; related mRNA-protein granules) affect TDP-43 phenotypes is unclear. Here, we determine that induction of TDP-43 expression in yeast results in the accumulation of SG-like foci that in >90% of cases become the sites where TDP-43 cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 68 publications
(110 reference statements)
1
24
0
Order By: Relevance
“…Since then, TDP-43 has been extensively studied relative to the formation of SGs as agents underlying pathological inclusions of the TDP-43 protein in the cytoplasm and nucleus. However, recent data point to a rather indirect relationship between the assembly of SGs and cytoplasmic aggregation of TDP-43 [ 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, TDP-43 has been extensively studied relative to the formation of SGs as agents underlying pathological inclusions of the TDP-43 protein in the cytoplasm and nucleus. However, recent data point to a rather indirect relationship between the assembly of SGs and cytoplasmic aggregation of TDP-43 [ 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…TDP-43 has been linked to the formation and regulation of mRNPs arising under stress conditions, namely stress granules [ 44 , 45 , 46 ]. Recent findings suggest that the occurrence of cytoplasmic TDP-43 inclusions is complex, and SGs may facilitate, but are not required for, the aggregation of TDP-43 in the cytoplasm [ 47 , 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…What is less clear at present, is whether this is linked to the formation of classic SGs, and potentially their persistence beyond the short term, or whether it is actually associated with the stress driven phase separation of non-RNA bound TDP-43, that explicitly does not get recruited to SGs. A recent study has demonstrated that impairment of SG assembly impairs the formation of TDP-43 foci in both acute and chronic stress paradigms, but crucially, did not completely prevent their formation, particularly in the chronic model, suggesting that while SGs may facilitate TDP-43 aggregation, TDP-43 proteinopathy can still develop through a SG-independent mechanism [105,110].…”
Section: Cell Typementioning
confidence: 99%
“…TDP-43 and FUS, however, are both RBPs containing prionlike domains as well as other shared domains. Like FUS, TDP-43 has been shown to colocalize with stress granules and p-bodies in yeast 36,70 which is interesting considering that TAF15 had no effect on TDP-43 toxicity. In this regard, it is notable that using the same Y2H assay, we could detect interaction of TAF15 with FUS but not with TDP-43 (data not sown).…”
Section: Discussionmentioning
confidence: 95%